The Relationship of Environmental Factors and Nutritional Status and The Incidence of ARI of Toddler in the Working Area of Donggala Public Health Center - Krisnasari, Sendhy; Aulia, Tresia; Syahadat, Dilla Srikandi; Marsellina, Marsellina; Wandira, Bertin Ayu (Journal of Health and Nutrition Research, 2022)
Acute Respiratory Tract Infection (ARI) is one of the contributors to the high morbidity and mortality rates of a toddler. ARIs are mostly suffered by the toddler in developing countries such as Indonesia, where the incidence is always high every year. The purpose of this study was to analyze the relationship between environmental factors and nutritional status with the incidence of ARI in children under five in the Donggala Community Health Center working area. This type of research is quantitative with a cross-sectional approach. The population in this research was 32,694 toddlers using the Slovin formula and obtained a sample of 100 toddlers. The sampling used was the Probability Sampling technique. The analysis used was Chi-Square. The variables that are significantly related to the incidence of ARI are nutritional status, smoking behavior, house ventilation, and residential density with a p-value < 0.05. Most of the respondents were malnourished, namely, 58%, had a high risk of exposure to cigarette smoke, which was 64%, and the house ventilation area which was included in the not good category was 57% and the residential density was included in the not eligible category at 59%. Prevention efforts to reduce the incidence of ARI in toddlers are by consuming nutritious food, education about house ventilation, and residential density, and increasing awareness of smoking behavior among parents.